Success Factors Associated With Health Information Systems Implementation: A Study of an Australian Regional Hospital - Sellitto , Carmine; Carbone , Daniel (Journal of Law and Governance, 2007)
This paper identifies five factors from the literature that are important for the successful implementation of health information systems (HIS). The HIS factors identified include stakeholder engagement, the support of management and local champions, understanding HIS imposed change, user training and the impact of government incentives. The paper further explored the introduction of a commonly used HIS (Medical Director®) in a regional Australian hospital and used the implementation factors as a guide for reporting stakeholder perceptions of the system. The implementation of the HIS in view of the systems users was a failure with all factors except the training issues poorly addressed. The study also reports the practicalities encountered with the system’s introduction and documents several new operational factors that were found to be associated with HIS implementation. Overall, the factors provided a sound criterion on which to judge the implementation performance (success or otherwise) of the HIS. The factors identified have the potential to be used as a guide by others who are engaged with information systems in the health area.